THE ISLAMIC WORLD IN THE CONTEXT OF MODERNIZATION IN THE ERA OF GLOBALIZATION: DYNAMICS AND PROSPECTS - Abuov, Amrekul; Orazaliyev, Bakhytzhan; Raimkulova, Aktoty (Scientific Journal of Pedagogy and Economics, 2020)
Geographical migration, intercultural and inter-civilizational interactions are not the only phenomena of the last decade of the XX century. The search for knowledge and the spread of the teachings of Allah (Christianity, Islam or Buddhism) and the search for livelihoods are among the reasons that trade and migration inevitably lead people to interact with one another. Wars and political arrogance, aimed at expanding the borders of the empire, and the constant attempt to rule the world are another factor in the reorganization of power to create global alliances. Given this, we can say that globalization is not a new phenomenon. After the Industrial Revolution and the rise of world capitalism, with the advent of lighter and faster communications, transport and other infrastructure, relations between the peoples of the world, cultural dialogue, interaction have grown and become more and more new every year. began to happen. To get an idea of the main features of modernization, it is necessary to refer to the experience of industrial societies in Europe and North America. Historical, scientific and technological progress has played a key role in the transformation of traditional European feudal society into a modern capitalist society. As a result of this progress, developing on the basis of pragmatism, the relations between new social classes, individuals and groups were reorganized, which underwent significant changes.